The Military and the Praetorian Regimes in Pakistan Politics: Political Usurpers or Protectors of an Incipient Democracy? (Journal of International Studies, 2020)
Pakistan seems to be a classic example of a praetorian state with regimes oscillating on both sides of the middle point of a military rule democracycontinuum, where the armed forces - often in collusion with the civil bureaucracy - is lodged in the centre of governance, dictating the actual course of actions, even when there is a civilian regime. Even now when Pakistan is supposedly going through a new round of parliamentary democracy, the military is likely to continue to play an important role in the politics of Pakistan, particularly in the backdrop of the military operations in Swat and surrounding districts which comes amid longstanding US pressure on its Muslim ally to root out AI-Qaeda and Taliban hideouts along the border with Afghanistan. Consequently, there are reasons to be worried that praetorian ism may persist in Pakistan.